Helping Others Results in Helping Yourself: How Well-Being Is Shaped by Agreeableness and Perceived Team Cohesion - Abira Reizer; Tal Harel; Uzi Ben-Shalom (Behavioral Sciences, 2023)
This longitudinal research explores team cohesion as a potential mediator explaining the associations between agreeableness as a personality trait and well-being. Additionally, the study examines whether the leader offering support moderates the mediating role of perceived group cohesion. The sample consists of male military personnel (N = 648) from six different units. The longitudinal design examined two time points, T1 and T2, during the soldiers’ training period. The PROCESS macro for SPSS was utilized to determine the significance of the moderator and the mediation effect. The results indicate that an agreeable personality and team cohesion at T1 predicted increased well-being at T2 (two months later). In addition, the moderated mediation hypothesis was significant, indicating that when leaders offered more support, the indirect link between an agreeable personality and well-being via team cohesion was stronger than when they offered less. The findings suggest that an agreeable personality and leader support are important in the organizational domain, and these variables promote well-being. By understanding the contribution of both external and internal sources of support to soldiers’ well-being, intervention plans can be developed to lessen the stressors of their mental well-being and help them reach their maximum potential.